UTILIZATION OF VARIOUS MICROORGANISMS IN CHEESE MAKING AS AN APPLICATION OF INDUSTRIAL BIOTECHNOLOGY - Ifa Ana Meilani; Ainun Nafiatus Ulfah, Alifia Hasna Azzah Fillah, Evria Asih, Hanasari Faida Pranama, Atip Nurwahyuna (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Cheese is a type of food produced by separating solid substances in milk through a process of thickening or coagulation. The cheese-making process generally involves the use of bacteria from the Actinobacteriaceae group. This study utilizes a literature review method, including the analysis of several relevant articles, and is further analyzed using a descriptive-analytical approach. The methodological steps involved searching Google with the keywords "cheese making" and "cheese microorganisms." Based on the discussion results, cheese production is not limited to cow's milk; cheese can also be processed from corn, soybeans, and red beans. The cheese-making process utilizes several probiotic bacteria such as Lactobacillus bulgaricus, Lactobacillus casei, and Streptococcus. The use of different starter bacteria can influence the characteristics of the resulting cheese. This research includes a total of 13 articles, comprising 5 articles on Lactobacillus bulgaricus, 5 articles on Lactobacillus casei, and 5 articles on Streptococcus.